CZY KAŻDY BILET ZAWSZE MUSI BYĆ ZNAKIEM LEGITYMACYJNYM, CZYLI ROZWAŻANIA O ZASADZIE ‘NUMERUS CLAUSUS’ PAPIERÓW WARTOŚCIOWYCH W POLSKIM PORZĄDKU PRAWNYM - Paweł Ochmann (Zeszyty Prawnicze)
The ‘Numerus Clausus’ Principle for Securitiesin the Polish Legal System Summary Most specialists on the doctrine of Polish private law hold that there is a numerus clausus principle for securities in Polish law, although it has not been specifically put into words in any act of legislation. According to the principle only those types of securities may be issued which are regulated by a statute. This means a prohibition on the issue of securities that have not been legally recognised. There are only a few opinions that say there is no numerus clausus on securities in Polish legal doctrine. This question has been the subject of a heated debate, which has attenuated over the last years. However, many issues have neither been scrutinised  nor even noticed. There are still several points worthy of consideration. The author’s aim in this paper is to review the arguments for and against numerus clausus; some of them have never been examined before. His analysis leads him to conclude that there is a numerus apertus (i.e. no restrictions) on some securities, such as bonds, while others such as shares, which endow their holder with special rights, are subject to legal restrictions. The article is an offshoot of research for a dissertation on private law conducted on an individual research programme supervised by Dr. M. Spyra at Collegium Invisibile in the 2013/2014 academic year.